Discussion - Toolis, Ronan (Scottish Archaeological Internet Reports, 2011)
Ploughing had removed occupation layers and all but the deepest features, in addition to removing artefacts from their original contexts. A fragment of willow charcoal produced a Mesolithic date although no features could be attributed to the period. Coherent clusters of features have been tentatively tied into specific chronological episodes of occupation (early Neolithic, late Neolithic-early Bronze Age, Iron Age and medieval).